PENGARUH BUDAYA KERJA, INTEGRITAS DAN KEPERCAYAAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA DOSEN UNIVERSITAS NEGERI JAKARTA - ENDANG SRI RAHAYU (Jurnal Ilmiah Econosains, 2017)
The objective research is to obtain information concerning to the effect of job culture, integrity, and trust towardteachers organizational citizenship behavior. The research was conducted by using survey method with path analysis in testing hypothesis. In this research, 115 from 950 teacher of teachers selected random sampling. The research was focused on four aspect; job culture, integrity, and trust towardteachers organizational citizenship behavior The data were colected with questionnaire and analyzed with path analysis. Result on the analyisis it is conculaded that (1) there the positive direct effect of job culturetowards organizational citizenship behavior, (2) there is positive direct effect of integrity towards organizational citizenship behavior, (3) there is positive direct effect of trust towards organizational citizenship behavior, (4) there is positive direct effect of job culture towards trust, (5) there is positive direct effect of integrity towards trust, and there is positive direct effect of job towards culture integrity Keywords: organizational citizenship behavior, organizational job culture, integrity, and trust